(untitled) (Global Journal of Medical Research, 2023)
Andrological Points Classification (CAP) Nelore Bulls (Bos Taurus Indicus) of Different Ages, Kept in Reproduction Central Summary-The objective of this study was to evaluate the reproductive potential of Nellore bulls at different ages, using the Andrological Points Classification system and to analyze the physical and morphological characteristics of the semen, when submitted to the cryopreservation protocol. Thus, 15 Nellore bulls were evaluated, divided into three groups according to age. The first group consisted of bulls aged ≤ 4 years, the second group of bulls aged 5 ≥ to ≤ 7 years, and the third group of bulls aged 8 ≥ to ≤ 10 years. From the evaluations performed, biometrics testicular and semen morphology, were relevant to determine the andrological classification by points (CAP index). For this purpose, the semen was collected using the electroejaculation method. And the results were expressed as mean and standard deviation.